First complete genome sequence of potato leafroll virus from Argentina - Barrios Baron, Maria Pilar; Agrofoglio, Yamila Carla; Delfosse, Veronica Cecilia; Nahirñak, Vanesa; Gonzalez De Urreta, Martin Salvador; Almasia, Natalia Ines; Vazquez Rovere, Cecilia; Sabio Y Garcia, Julia Veronica (2017)
In this study, we determined for the first time the complete genomic sequence of an Argentinian isolate of Potato leafroll virus (PLRV), the type species of the genus Polerovirus. The isolate sequenced came from a Solanum tuberosum plant that had been naturally infected with the virus. Isolate PLRV-AR had a nucleotide sequence identity between 94.4 and 97.3% with several known PLRV isolates worldwide.